A Proposed Genus Boundary for the Prokaryotes Based on Genomic Insights - Qin, Qi-Long; Xie, Bin-Bin; Zhang, Xi-Ying; Chen, Xiu-Lan; Zhou, Bai-Cheng; Zhou, Jizhong; Oren, Aharon; Zhang, Yu-Zhong (Journal of bacteriology, 2014)
Genomic information has already been applied to prokaryotic species definition and classification. However, the contribution of the genome sequence to prokaryotic genus delimitation has been less studied. To gain insights into genus definition for the prokaryotes, we attempted to reveal the genus-level genomic differences in the current prokaryotic classification system and to delineate the boundary of a genus on the basis of genomic information. The average nucleotide sequence identity between two genomes can be used for prokaryotic species delineation, but it is not suitable for genus demarcation. We used the percentage of conserved proteins (POCP) between two strains to estimate their evolutionary and phenotypic distance. A comprehensive genomic survey indicated that the POCP can serve as a robust genomic index for establishing the genus boundary for prokaryotic groups. Basically, two species belonging to the same genus would share at least half of their proteins. In a specific lineage, the genus and family/order ranks showed slight or no overlap in terms of POCP values. A prokaryotic genus can be defined as a group of species with all pairwise POCP values higher than 50%. Integration of whole-genome data into the current taxonomy system can provide comprehensive information for prokaryotic genus definition and delimitation.